Establishing a critical nitrogen dilution curve for estimating nitrogen nutrition index of potato crop in tropical environments - Soratto, Rogério P. [UNESP]; Sandaña, Patricio; Fernandes, Fabiana M. [UNESP]; Fernandes, Adalton M. [UNESP]; Makowski, David; Ciampitti, Ignacio A. (Elsevier, 2022)
The critical nitrogen (N) dilution curve (CNDC) (Nc = A1W-A2) and the N nutrition index (NNI) have shown to be a robust diagnostic tool to assess crop N status. Several CNDCs were established for potatoes (Solanum tuberosum L.) in various conditions. However, it is difficult to know if these different CNDCs reflect a true variability across genotype × environment × management (G×E × M) scenarios, or are rather linked to estimation errors. Therefore, the aims of this study were to (i) estimate and compare CNDCs via a Bayesian statistical approach for different G×E × M scenarios in tropical environments and (ii) assess the uncertainty in the relationship between tuber yield and NNI. Field experiments were conducted in three site-years (SYs) in the southeastern region of Brazil. Treatments consisted of two potato cultivars (Agata and Electra) and five N fertilization managements [differing in the N rates (0 −320 kg N ha-1) and/or application timings]. Based on 95% credibility intervals, we found no significant differences between CNDCs across G×E × M scenarios assessed and thus derived a single generic CNDC for both cultivars and all SYs defined by Nc = 3.86 W-0.34. This global CNDC was used to compute NNI and discriminate tuber yields obtained under N-limiting and non-N-limiting conditions. An uncertainty analysis revealed that critical NNI threshold values for the tuber yield response to N management were not statistically different among G×E × M scenarios. Therefore, these results support the use of a unique CNDC for estimating the N status (NNI) of potato crop in tropical environments. We found no evidence of the need for SY- or cultivar-specific CNDCs. Future studies should evaluate N dilution curves and NNI for potato across different production environments worldwide.
Keywords: Bayesian; N management; NNI; Solanum tuberosum; Tuber yield